Performance Evaluation of Gauss-Markov Mobility Model in Hybrid LTE-VANET Networks - Doan Perdana; Rendy Munadi; Robby C. Manurung (Universitas Ahmad Dahlan, 2017)
Vehicular Ad-hoc Network (VANET) developed based on mobile ad-hoc networks (MANET). VANET have different characteristics than MANET, on VANET mobile node (MN) moves faster, topology changes dynamically. The previous research shows that the model of mobility affects to the network performance. In this paper, the Gauss-Markov mobility model used to illustrate the motion of the MN, which illustrates changes of acceleration, speed, location, and direction at any time. This paper enriches the evaluation of the performance of Gauss-Markov mobility model on LTE-VANET hybrid network, by evaluating various network performance metrics, particularly, packet delivery ratio (PDR), throughput, and delay. This research evaluated the Gauss-Markov mobility model and performed with the number of nodes and randomness index (α) that varies by utilizing NS-3 software. The results show that there is a strong correlation between PDR, throughput, and delay with the addition number of MNs. Based on the simulation result, the hybrid LTE-VANET produce better delay compared to pure VANET. The average delay is smaller 40% compared to pure VANET. This simulation also concludes that different value of alpha on Gauss-Markov mobility model does not influence PDR, throughput, and delay.